1997
DOI: 10.2105/ajph.87.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Sex trading and psychological distress among women recruited from the streets of Harlem.

Abstract: OBJECTIVES: This study examines the relationship between sex trading and psychological distress and the implications of that relationship for prevention of human immunodeficiency virus among a sample of young women recruited from the streets of Harlem. METHODS: Interviews were conducted with 346 predominantly drug-using women, aged 18 to 29 years, of whom 176 had exchanged sex for money or drugs in the previous 30 days and were categorized as "sex traders." Psychological distress was measured by using the Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
4
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 40 publications
5
114
4
4
Order By: Relevance
“…Impulsivity, hypersexuality, and other manic symptoms, especially in the context of substance abuse (Salloum et al, 2002), may further explain this relationship. As in other high-risk samples (El-Bassel et al, 1997;Goodman and Fallot, 1998;Vaddiparti et al, 2006), sex trading was more likely among cocaine-dependent participants. The direct effects of stimulants on sexual functioning, including increased stimulation and libido, likely contribute to both sex trading and sex with prostitutes (Rawson et al, 2002;Volkow et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…Impulsivity, hypersexuality, and other manic symptoms, especially in the context of substance abuse (Salloum et al, 2002), may further explain this relationship. As in other high-risk samples (El-Bassel et al, 1997;Goodman and Fallot, 1998;Vaddiparti et al, 2006), sex trading was more likely among cocaine-dependent participants. The direct effects of stimulants on sexual functioning, including increased stimulation and libido, likely contribute to both sex trading and sex with prostitutes (Rawson et al, 2002;Volkow et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…Physical health problems associated with selling or trading sex include Hepatitis B and C (Harcourt, Beek, Heslop, McMahon, & Donovan, 2001), -Bassel, et al, 1997;Flowers, 2001), and other sexually transmitted infections (Jeal & Salisbury, 2004). While there is limited research regarding mental health symptoms specific to DMST victims, a recent descriptive study of a residential program for sexually exploited children found that among the 13 residents with completed mental health records, residents had an average of at least two primary mental health disorders, most commonly PTSD (n = 6) and depression (n = 4) (Twill, Green, & Traylor, 2010).…”
Section: Negative Consequences Of Dmst Victimizationmentioning
confidence: 99%
“…Illicit substance use often place individuals within "underground" networks, increasing the likelihood of unwanted sexual activity and violence. 16 Sexual partners are also more likely to be substance users. Research has shown that drug-involved couples are vulnerable to high levels of stress related to poverty, underemployment, and limited social supports.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showing that increases in power are associated with safer sexual behaviors led the authors to hypothesize that the SRPS subscales will each be inversely associated with sexual risk, that is higher scores on relationship control and decision-making dominance subscales would be associated with fewer unprotected sexual occasions. Additional factors associated with increased sexual HIV risk, including age and race/ethnicity, 29 economic dependence, [15][16][17] condom use intention, 30,31 sexual concurrency, [32][33][34] and partner abuse, [35][36][37][38] were included in the analytic model to assess the unique contribution relationship power has on unprotected sex. Findings contribute to the understanding of how multidimensional heterosexual power dynamics influence unprotected sexual behavior with particular attention to a subpopulation of women who may be at higher risk for HIV transmission.…”
Section: Introductionmentioning
confidence: 99%